Impact of urban productive safety net programme on poverty reduction and food security: Evidence from major cities of Eastern Ethiopia (Dire Dawa, Harar and Jigjiga) - Salah Mohammed Abdulahi; Habtamu Legese Feyisa; Dereje Degu Ayen (Food and Energy Security, 2024)
Abstract Different social protection programs are designed in low‐income countries to eradicate poverty and improve the food security of poor people. Currently, the Urban Productive Safety Net Program (UPSNP) is designed to support those who are living in poverty and face food insecurity with predictable and reliable support through food, cash, or vouchers. However, limited empirical evidence has been presented about the significant impact of the program on the well‐being of households who participated in the program and the factors that affect the households' decision to participate in the program. Hence, this study aims to evaluate the impact of participation in UPSNP on well‐being using household survey data gathered from three main cities of Ethiopia: Dire Dawa, Harar, and Jigjiga in 2022. This study employed both propensity score matching (PSM) and endogenous switching regression (ESR) models to assess the impact of the UPSNP. The result shows that the probability of a household's participation decision is determined by the age of the household head, number of children, savings, house ownership, employment status of the household head, and shock. Furthermore, we found a consistently positive impact across models, indicating that participation in UPSNP reduces poverty and increases food security of households.